Ian Milligan, Rebel Youth: 1960s Labour Unrest, Young Workers, and New Leftists in English Canada - Lexier, Roberta (Historical Studies in Education / Revue d'histoire de l'éducation, 2015)
The article reviews the book, "Rebel Youth: 1960s Labour Unrest, Young Workers, and New Leftists in English Canada," by Ian Milligan.